High-Capacity Adenoviral Vectors Permit Robust and Versatile Testing of DMD Gene Repair Tools and Strategies in Human Cells - Marcella Brescia; Josephine M. Janssen; Jin Liu; Manuel A. F. V. Gonçalves (Cells, 2020)
Duchenne muscular dystrophy (DMD) is a fatal X-linked muscle wasting disorder arising from mutations in the ~2.4 Mb dystrophin-encoding DMD gene. RNA-guided CRISPR-Cas9 nucleases (RGNs) are opening new DMD therapeutic routes whose bottlenecks include delivering sizable RGN complexes for assessing their effects on human genomes and testing ex vivo and in vivo DMD-correcting strategies. Here, high-capacity adenoviral vectors (HC-AdVs) encoding single or dual high-specificity RGNs with optimized components were investigated for permanently repairing defective DMD alleles either through exon 51-targeted indel formation or major mutational hotspot excision (>500 kb), respectively. Firstly, we establish that, at high doses, third-generation HC-AdVs lacking all viral genes are significantly less cytotoxic than second-generation adenoviral vectors deleted in E1 and E2A. Secondly, we demonstrate that genetically retargeted HC-AdVs can correct up to 42% ± 13% of defective DMD alleles in muscle cell populations through targeted removal of the major mutational hotspot, in which over 60% of frame-shifting large deletions locate. Both DMD gene repair strategies tested readily led to the detection of Becker-like dystrophins in unselected muscle cell populations, leading to the restoration of β-dystroglycan at the plasmalemma of differentiated muscle cells. Hence, HC-AdVs permit the effective assessment of DMD gene-editing tools and strategies in dystrophin-defective human cells while broadening the gamut of DMD-correcting agents.